Natural cutaneous anthrax infection, but not vaccination, induces a CD4(+) T cell response involving diverse cytokines. - Ingram,RJ; Ascough,S; Reynolds,CJ; Metan,G; Doganay,M; Baillie,L; Williamson,DE; Robinson,JH; Maillere,B; Boyton,RJ; Altmann,DM (Cell and Bioscience, 2015)
BACKGROUND: Whilst there have been a number of insights into the subsets of CD4(+) T cells induced by pathogenic Bacillus anthracis infections in animal models, how these findings relate to responses generated in naturally infected and vaccinated humans has yet to be fully established. We describe the cytokine profile produced in response to T cell stimulation with a previously defined immunodominant antigen of anthrax, lethal factor (LF), domain IV, in cohorts of individuals with a history of cutaneous anthrax, compared with vaccinees receiving the U.K. licenced Anthrax Vaccine Precipitated (AVP) vaccine. FINDINGS: We found that immunity following natural cutaneous infection was significantly different from that seen after vaccination. AVP vaccination was found to result in a polarized IFNγ CD4+ T cell response, while the individuals exposed to B. anthracis by natural infection mounted a broader cytokine response encompassing IFNγ, IL-5, -9, -10, -13, -17, and -22. CONCLUSIONS: Vaccines seeking to incorporate the robust, long-lasting, CD4 T cell immune responses observed in naturally acquired cutaneous anthrax cases may need to elicit a similarly broad spectrum cellular immune response.